IMPACT OF COGNITIVE IMPAIRMENT ON QUALITY OF LIFE IN ELDERLY PATIENTS WITH HYPERTENSIVE ENCEPHALOPATHY (World Bulletin of Public Health, 2025)
The article examines the effect of the presence of cognitive impairment on the severity of anxiety and depression in elderly and senile patients with stage 2 and 3 hypertension. Using the literature data, it was found that cognitive impairment has a detrimental effect on the quality of life of patients, as well as the fact that patients with depression should carefully conduct a study of the cognitive sphere in order to choose the right treatment tactics
Keywords: Cognitive Impairment; Depression